GPER-1 Expression Decreases During Breast Cancer Tumorigenesis. (1st June 2013) - Ignatov, Tanja; Weißenborn, Christine; Poehlmann, Angela; Lemke, Antje; Semczuk, Andrzej; Roessner, Albert; Costa, Serban Dan; Kalinski, Thomas; Ignatov, Atanas
Abstract : GPER-1 protein expression was immunohistochemically examined in 164 primary breast cancer specimens and their matched normal breast epithelium. GPER-1 down-regulation correlated significantly with increased histological grading ( p = .015), lymph node metastases ( p = .032), and negative estrogen receptor status ( p = .018). The decrease of GPER-1 expression in breast cancer tissue, relative to normal tissue, was associated with poor overall survival ( p = .043) and disease-free survival ( p = .037) and remained a significant unfavorable factor in multivariate analysis for DFS (HR = 1.569; 95% CI, 1.024–2.797; p = .041) and OS (HR = 2.082; 95% CI, 1.248–4.773; p = .039). Thus aberrant GPER-1 expression seems to be an important factor in breast cancer progression.